2020
DOI: 10.1002/nop2.563
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and perceptions about research misconduct among graduate nursing students

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, this article assessed the relationship among mental disorder awareness and religious interest where religion is frequently disregarded in prior studies Additionally, there were not any available study regarding correlation of religion and stigma toward mental ill patients. Eventually, provided the religious raising occurrence and huge figures of people with instability issues within the population ( Shen et al., 2006 ; Abuhammad et al., 2020 ). These outcomes support specifying a possible corroborating of people following religion on regular basis and organizations may influence within the prerequisite of population-based mental illness assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this article assessed the relationship among mental disorder awareness and religious interest where religion is frequently disregarded in prior studies Additionally, there were not any available study regarding correlation of religion and stigma toward mental ill patients. Eventually, provided the religious raising occurrence and huge figures of people with instability issues within the population ( Shen et al., 2006 ; Abuhammad et al., 2020 ). These outcomes support specifying a possible corroborating of people following religion on regular basis and organizations may influence within the prerequisite of population-based mental illness assistance.…”
Section: Discussionmentioning
confidence: 99%
“…These codes provide people with behaviors within some acceptable borders (9) . In Jordan, a study of nursing students at Jordan University of Science and Technology showed a higher perception of the dangers of research misconduct among graduate nursing students who were more religious (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Globally, religiosity is considered a dimension of every individual's life ( Abuhammad et al, 2020a , Abuhammad et al, 2020b ) including children and people with mental illnesses. Religiosity can be described as the degree of individual commitment and the attitudes and behaviours that show respect of higher nonhuman power ( Ketola and Stein, 2013 ).…”
Section: Introductionmentioning
confidence: 99%